Lassa fever risk perception and "one-health. considerations associated with rodent control practices in a Nigerian University (2017)
Lassa fever has an enormous public health impact in West Africa with thousands of human cases reported annually. The disease is both endemic and zoonotic in Nigeria and the Mano River Union countries of Sierra Leone, Guinea and Liberia in West Africa. The University of Benin, Benin City and its environs, are located within an epicentre of Lassa fever (LF) in the south-south region of Nigeria. Personal and public considerations about safety of agricultural products and the general living environment were investigated among students and staff within the university community. Selected socio-economic variables were evaluated. Results indicated that higher education was associated with animal hygiene related knowledge of LF (73.4%), compared to 37.3% of respondents with basic education who demonstrated poor knowledge of transmission of the disease (p<0.0001). High risk awareness was linked to one-health information dissemination on LF in media and campaigns (75.5%), in comparison with native oral transmission of information about the disease (24.5%). Risk perception was significantly associated with measures aimed at rat and various species of mice control amongst respondents (p=0.022). Ability of respondents to recognize rats, including Mastomys natalensis complex, the carrier of LF-virus within residential dwellings (71.1%) and contact of rats with human food (9.6%) elucidate the persistent public health threat in endemic areas. Cultural practices such as eating of rats (4.4%) and rat hunting practices (6.1%) further corroborates the value of a one-health agenda for LF control. This paper presents the control of rats and mice within the university campus as an animal hygiene and one-health agenda, which incorporates multiple socio-cultural factors for a more robust LF prevention mode